Calidad de Atención por parte del personal Médico y de Enfermería a pacientes geriátricos hospitalizados en los servicios de Medicina Interna y Cirugía del Hospital Regional Isidro Ayora de Loja. - Montoya Pasaca, Katiuska Ivanova (2013)
The human aging is a natural process that occurs throughout the life cycle. Reflect upon the prejudices we may have and improve our training on it will help us question our habits and improve the treatment of older people we serve. The duty of care responsibility of all trained professionals in nursing homes, this care means providing humane care and scientifically accurate, step into the shoes of the other, explore their emotions, listen, knowing your thoughts, meet their needs and improve their problem health. This research makes reference: "QUALITY OF CARE FROM THE STAFF DOCTOR AND OF NURSING TO PATIENTS GERIATRIC HOSPITALIZED IN THE SERVICES OF MEDICINE INTERNAL AND SURGERY OF THE HOSPITAL REGIONAL ISIDRO AYORA OF LOJA". Being its main objective determine that perception of quality of care provided by medical staff and nurses, have geriatric inpatients in such services. To expire with this, a prospective investigation was implemented and trasversal, carried out in 58 major adult patients hospitalized in the Services of Internal Medicine and Surgery of the regional Hospital Isidro Ayora, by means of the application a survey for information compilation. Is he came to the conclusion that: 41% of users have a good perception of the quality of attention despite the shortfall of existing staff and resources. Referring to the warmth in the service, the 38% indicated that this is always provided and the 14% noted that was not effected. In regard to the satisfaction of the warmth and quality received in the attention, it was found that 35% felt very satisfied, and 36% showed a slight satisfaction. Key words: Quality of care, Older adults, Aging.